A Comparative Study of Hybrid Adaptive Neuro-Fuzzy Inference Systems to Predict the Unconfined Compressive Strength of Rocks - Annabelle Graham; Emma Scott (Advances in Engineering and Intelligence Systems)
The precise estimation of Unconfined Compressive Strength (UCS) in rock samples is paramount for the effective planning and execution of mining and civil engineering projects. However, the inherent variability and discontinuity within rock masses present challenges in obtaining accurate physico-mechanical data. In this study, the application of Adaptive Neuro-Fuzzy Inference Systems (ANFIS) investigate as a cost-efficient and reliable approach to predict UCS from Bulk Density (BD), Bulk Tensile Strength (BTS), dry density (DD) test, p-wave velocity test (Vp), Schmidt hammer rebound number (SRn), and point load index test (Is(50)). ANFIS excels in effortlessly amalgamating expert knowledge using linguistic rules and empirical data, thus enhancing model interpretability and transparency, qualities profoundly esteemed in the geosciences. Furthermore, it allows for parameter fine-tuning optimizing model performance, as evidenced by its enhanced performance with the Mountain Gazelle Optimizer (MGO) and Adaptive Opposition Slime Mould Algorithm (AOSMA) in this study. Models were trained with 70% of the dataset, and the performance of the models was tested with 30% of the dataset. Performance indices such as R2, RMSE, NMSE, MAE, and n_10 index were used to assess the predictive capability of models indicating that ANAS with maximum  ÿ R2all=0.987 and minimum RMSEall=3.103, has the most optimal prediction performance for practical applications.